Analysis of the Effect of Operational Efficiency, Good Corporate Governance, and Inflation on Financial Distress (Case Study on ISSI 2019-2023) - Hasan, Nadya Atiqoh; Berakon, Izra (Review on Islamic Accounting, 2025)
This study aims to analyze the influence of operational efficiency, good corporate governance (GCG), and inflation on financial distress in consumer cyclical sector companies listed on the Indonesian Sharia Stock Index (ISSI) from 2019 to 2023. Financial distress is measured using the modified Altman Z-Score model, while GCG variables are proxied by institutional ownership, managerial ownership, board of directors, board of commissioners, and audit committee. Operational efficiency is measured by Total Asset Turnover (TATO), and inflation is calculated based on data from the Central Statistics Agency. This research employs panel data with a multiple linear regression approach and purposive sampling to select 18 companies as samples. The results indicate that managerial ownership and operational efficiency have a significant positive effect on financial distress, while the board of directors has a significant negative effect. Meanwhile, institutional ownership, board of commissioners, audit committee, and inflation do not significantly influence financial distress. Control variables such as firm size and leverage also show significant effects.